Temporal correlation between differentiation factor expression and microRNAs in Holstein bovine skeletal muscle. (13th July 2016) - Miretti, S.; Volpe, M. G.; Martignani, E.; Accornero, P.; Baratta, M.
Abstract : Satellite cells are adult stem cells located between the basal lamina and sarcolemma of muscle fibers. Under physiological conditions, satellite cells are quiescent, but they maintain a strong proliferative potential and propensity to differentiate, which underlies their critical role in muscle preservation and growth. MicroRNAs (miRNAs) play essential roles during animal development as well as in stem cell self-renewal and differentiation regulation. MiRNA-1, miRNA-133a and miRNA-206 are closely related muscle-specific miRNAs, and are thus defined myomiRNAs. MyomiRNAs are integrated into myogenic regulatory networks. Their expression is under the transcriptional and post-transcriptional control of myogenic factors and, in turn, they exhibit widespread control of muscle gene expression. Very little information is available about the regulation and behavior of satellite cells in large farm animals, in particular during satellite cell differentiation. Here, we study bovine satellite cells (BoSCs) undergoing a differentiation process and report the expression pattern of selected genes and miRNAs involved. Muscle samples of longissimus thoracis from Holstein adult male animals were selected for the collection of satellite cells. All satellite cell preparations demonstrated myotube differentiation. To characterize the dynamics of several transcription factors expressed in BoSCs, we performed real-time PCR on complementary DNA generated from the total RNA extracted from BoSCs cultivated in growth medium (GM) or in differentiation medium (DM) for 4 days. In the GM condition, BoSCs expressed the satellite cell lineage markers as well as transcripts for the myogenic regulatory factors. At the time of isolation from muscle, PAX7 was expressed in nearly 100% of BoSCs; however, its messenger RNA (mRNA) levels dramatically decreased between 3 and 6 days post isolation ( P <0.01). MyoD mRNA levels increased during the 1st day of cultivation in DM (day 7; P <0.02), showing a gradual activation of the myogenic gene program. During the subsequent 4 days of culture in DM, several tested genes, including MRF4, MYOG, MEF2C, TMEM8C, DES and MYH1, showed increased expression ( P <0.05), and these levels remained high throughout the culture period investigated. Meanwhile, the expression of genes involved in the differentiation process also miRNA-1, miRNA-133a and miRNA-206 were strongly up-regulated on the 1st day in DM (day 7; P <0.05). Analysis revealed highly significant correlations between myomiRNAs expression and MEF2C, MRF4, TMEM8C, DES and MYH1 gene expression ( P <0.001). Knowledge about the transcriptional changes correlating with the growth and differentiation of skeletal muscle fibers could be helpful for developing strategies to improve production performance in livestock.